2010
DOI: 10.1002/ccd.22347
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopic analysis of different drug eluting stents after failed implantation: From nearly undamaged to major damaged polymers

Abstract: Placement of drug eluting stents in tortuous vessels and/or calcified lesions could cause major surface damage by scratching and scraping of the polymer or drug by the arterial wall, even before implantation. There were remarkable differences among the stents examined, only minor damage with the Cypher, Taxus Costar, Janus, and Xience V, whereas the Endeavor, the Yukon, and the Janus DES showed large areas of surface injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(87 citation statements)
references
References 40 publications
(74 reference statements)
0
85
0
2
Order By: Relevance
“…14 Other concerns with regard to the potential for polymer disruption involve the percutaneous coronary intervention procedure itself. Wiemer et al 54 demonstrated that in DES that had failed to be delivered to the intended implantation site in tortuous calcified lesions, significant damage and cracking of the polymer had occurred to varying extents with multiple types of second-generation DES. Scanning electron microscopy revealed many cases of deep damage to the polymer with exposure of the bare metal, in particular, the Endeavor RX stents showed up to 20% damage to the surface area.…”
Section: Polymer Disruption Peeling and Crackingmentioning
confidence: 99%
“…14 Other concerns with regard to the potential for polymer disruption involve the percutaneous coronary intervention procedure itself. Wiemer et al 54 demonstrated that in DES that had failed to be delivered to the intended implantation site in tortuous calcified lesions, significant damage and cracking of the polymer had occurred to varying extents with multiple types of second-generation DES. Scanning electron microscopy revealed many cases of deep damage to the polymer with exposure of the bare metal, in particular, the Endeavor RX stents showed up to 20% damage to the surface area.…”
Section: Polymer Disruption Peeling and Crackingmentioning
confidence: 99%
“…This is supported by the fact that our trial, which included the same rate of diabetic patients and lesion complexity as DELIVER, gave the same results. Increase in lesion complexity may indeed wipe off the drug 28 A preclinical study of DELIVER has also estimated that ≈40% of drug is lost during stent delivery of PF-PES. 11 Cracking drug on stent surface may result in nonuniform local drug distribution with subsequent abnormal neointimal hyperplasia, as observed in DELIVER and in the present trial.…”
Section: Discussionmentioning
confidence: 99%
“…27.10 ). The diameter differences were de fi nitely greater than the coating thicknesses, which are in the range of a few microns only [ 25 ] . The larger stent pro fi les, and probably differing friction properties, of DES compared to BMS bear the risk of a decrease in trackability and crossability of the stent systems.…”
Section: Special Parameters Of Desmentioning
confidence: 99%
“…The technical characterization concentrates on potential particle release during stent delivery, expansion, and cyclic loading as well as on the assessment of coating integrity. Surface cracking occurs in many DES during delivery, but to a very different extent [ 25 ] . Even if the study had limitations due to the extraordinary stresses experienced by the stent during failed delivery, the observed coating defects and damages are alarming.…”
Section: Special Parameters Of Desmentioning
confidence: 99%